Revolutionizing the Art of Calligraphy with Kelk Software: Embracing a New Digital Age in Calligraphic Writing - Dariyadi, Moch Wahib (Universitas Negeri Malang, 2022)
Proficiency in Arabic calligraphy was once confined to a select few blessed with innate talent or those who underwent formal or informal education. Mastery of this art was achieved through either inherent abilities and rigorous training or persistent self-learning and dedication. However, in today's technological landscape, the challenges associated with learning calligraphy can be surmounted through the aid of software applications that streamline and enhance the learning process. One such solution is the utilization of the